Factors Supporting The Position And Role Of Minangkabau Women In Resolving Heritage Conflicts In West Sumatra - Imam Mahardinata; Nawir Yuslem; Asmuni Asmuni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Conflict resolution of heritage is a problem that often occurs in Indonesian society. This conflict usually occurs due to disagreements in dividing inherited property between family members. In West Sumatra, Minangkabau women are essential in resolving inheritance conflicts. This article will explain the factors that support the position and role of Minangkabau women in resolving heritage conflicts in West Sumatra. This research is empirical legal research or (socio-legal research) with socio-empirical studies with qualitative research. The approach method used in this study is part of legal pluralism (mix or mix), including philosophical, sociological, phenomenological, and legal anthropological approaches. This article aims to provide an understanding of the role and position of Minangkabau women in resolving heritage conflicts in West Sumatra. The factors that support their role are Economic, Educational, Psychological, and Social factors. It is hoped that this article can provide a better insight into the importance of the role of women in resolving inheritance conflicts, as well as provide proper recognition for Minangkabau women for their contributions to society